Determinants of Vaginal Microbiota Composition - Moosa, Yumna; Kwon, Douglas; de Oliveira, Tulio; Wong, Emily B. (Frontiers in Cellular and Infection Microbiology, 2020)
There is increasing evidence that the composition of a woman's vaginal microbiota significantly influences her sexual and reproductive health, including her risk of miscarriage, preterm birth, HIV and other sexually transmitted infections. Efforts to modulate the vaginal microbiota using antibiotic or probiotic therapy have shown limited lasting or reliable success. To explore the natural dynamics and causal pathways responsible for heterogeneity of vaginal microbiota composition we review the existing literature on its determinants, from the perspective of microorganism- and host-related factors. We then discuss how molecular approaches can be harnessed to advance our understanding of individual and population-level vaginal microbiota composition patterns. Work has been done to investigate determinants of microbial composition patterns in other body niches, but very little in the female genital tract so far. There is an urgent need to better understand vaginal microbiota composition patterns, across the lifespan, outside of the context of sexual health clinics, and in Sub-Saharan African women in whom vaginal microbiota composition may be a risk factor for HIV acquisition. More work is needed to clarify causal relationships between clinical symptoms, host genetic, host behavior, and molecular vaginal microbiota profiles. These insights will lay the groundwork for novel and targeted interventional approaches to improve women's sexual and reproductive health.